Konsolidasi Tanah untuk Penyelesaian Konflik di Tutupan Jepang dalam Kerangka Reforma Agraria: Studi Kasus Kalurahan Parangtritis, Bantul - Putraningtyas, Margaretha Elya Lim; Martini, Sri; Rohayati, Titin (Diploma IV Pertanahan Sekolah Tinggi Pertanahan Nasional, 2024)
The Japanese Government initiated the Japanese Covered Land Conflict in Parangtritis Subdistrict, Kapanewon Kretek, Bantul Regency by seizing community land, marking it in red ink on the Ledger Book/Letter C and labeling it as